Akram Khan: Dancing New Interculturalism, Royona Mitra (2015). Issue 1 (1st August 2020) - Madhavan, Arya
Akram Khan: Dancing New Interculturalism, Royona Mitra (2015)London: Palgrave Macmillan, 197 pp., ISBN 978-1-34948-363-1, p/bk, £44.58